Developing an in vitro validated 3D in silico internal carotid artery sidewall aneurysm model - Yi, Hang; Yang, Zifeng; Johnson, Mark; Bramlage, Luke; Ludwig, Bryan (Frontiers in Physiology, 2022)
Direct quantification of the various hemodynamic factors applied to a cerebral aneurysm remains inaccessible due to lack of technologies to measure the flow field within them precisely. This study aimed to develop an in-vitro validated 3D in-silico patient-specific internal carotid artery sidewall aneurysm (ICASA) model using particle image velocimetry (PIV) for flow field quantifications and computational fluid dynamics (CFD) simulations. Specifically, the flow field characteristics, i.e., blood flowrate, normalized velocity profiles, flow streamlines, and vortex locations, have been compared at representative time instants of the transient pulsatile flows in two designated regions of the ICASA model, respectively. One region is in the artery inlet close to the aneurysm sac, the other one is across the middle of the aneurysmal sac. The results indicate that the developed CFD model presents good agreements with the results from parallel PIV and flowrate measurements, with the relative differences smaller than 0.33 % in volumetric flowrate in the internal carotid artery and relative errors smaller than 9.52% in averaged velocity magnitudes in the complex aneurysmal sac. However, small differences between CFD simulations and PIV measurements in the near wall regions were observed due to the factors of slight differences in the 3D printed geometry, light reflection and refraction near the wall, and flow waveform uncertainties. The in-vitro validated in-silico study provides a typical model and guidance for other researchers to investigate the hemodynamic effects on human cerebral aneurysms, which can be further adopted to conduct statistical analysis of the hemodynamic factors on the pathophysiology of different cerebral aneurysms.